A New Radar Echo Generation Model for Ultra-Low Altitude Targets in Far-Field Conditions - Zhao Long Wang; Chuang Ming Tong; Tong Wang; Yi Jin Wang; Qing Kuan Wang (International Journal of Antennas and Propagation)
This paper proposed a new radar echo simulation method for ultra-low altitude targets in far-field conditions. Based on the electromagnetic (EM) scattering calculation of target and environment, combined with the weighted four-path model, the scattering data of target, environment, and multipath are obtained. The Range-Doppler ring partitioning method is used to determine the size of the minimum resolution units, and then the environment is divided into several scattering elements. By using the method of temporal decomposition, the wide-time pulse is decomposed into a plurality of narrow pulse signals, and the narrow pulses act on scattering elements with different distances and orientations in space. The total echo is obtained by a linear superposition of the responses of each scattering unit. In addition, the numerical results with different parameters, including signal bandwidths, target types, and target height, are simulated and analysed. The simulation results demonstrate that the proposed method can provide a better description of the scattering characteristics of sea-skimming targets in complex scenes in far-field conditions. Meanwhile, it can be applied to the detection and recognition of ultra-low altitude targets above the sea surface.